ANALISIS POTENSI DAN PRIORITAS PENGEMBANGAN PARIWISATA DI KOTA MEDAN - Puput gloria zega; Theresia Asmirandah; Deswita Syahputri; Will Bright Naibaho; Sahala Fransiskus Marbun (Jurnal Salome : Multidisipliner Keilmuan, 2025)
This study aims to analyse the potential of tourist destinations, tourist perceptions, and tourism development priorities in the city of Medan. Four main destinations, namely Maimun Palace, Al-Mashun Grand Mosque, Tjong A Fie Mansion, and Rahmat International Wildlife Museum & Gallery, were the focus of the study given their strategic role as icons of urban tourism based on history, religion, and education. The research method used was a descriptive qualitative approach through field observations, in-depth interviews, and documentation studies. The results of the study show a significant increase in the number of tourist visits in 2024. The social, cultural, and economic potential of the four destinations has been proven to support the sustainable development of the tourism industry. Tourists' perceptions of the quality of the destinations tend to be positive, although several weaknesses were found, particularly in terms of service, cleanliness, vendor management, and professionalism in management. The study concludes that tourism development in Medan requires an integrative strategy involving infrastructure improvements, strengthened digital promotion, community empowerment, and multi-stakeholder collaboration to create highly competitive destinations.